Teaching Personal Protection and Safety to Middle School Students in Physical Education: Editor: Ferman Konukman. Issue 5 (12th June 2020) - Follo, Giovanna
Abstract : The purpose of this article is to continue to fill the gaps in personal protection and safety programs that are being taught in middle school. The following teaching tips can enhance the effectiveness of students' ability to survive and escape confrontations, their confidence in doing so, and increase their feelings of self-empowerment. The four main areas of discussion are program, myth busting, teaching progression, and realistic drills.